Body weight had highest correlation coefficient with heart girth around the chest under the same farmers feeding conditions for Arsi Bale sheep - Ashebir Worku (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2019)
The study was conducted in Adami Tulu Jido Kombolcha and Bora districts from east Shoa zone as well as Kofele and Asasa from west Arsi zone of Oromia regional state. The objective of this study was to determine the best regression model for live weight estimation to be used by farmers without the use of weighing scale for indigenous sheep breed found in East Shoa and West Arsi zone of Oromia Regional State. Purposive and simple random sampling was employed to select the study kebeles and all the sheep for body weight and linear body measurements. Thus body weight and linear body measurements were assessed from 600 heads of sheep. Body weight of the rams and ewes varied across the age groups. Natural pasture, crop residues, crop aftermath local brewery wastes too are paramount importance. The regression analysis to predict body weight from linear measurements indicated body weight is influenced by morphometrical measurements which included body length, chest girth and the other leaner measurements. The body weight had highest correlation coefficient with heart girth (CG) around the chest (r > 0.80) compared with other body measurements. The stepwise regression models indicated that heart girth singly accounted highest variation (more than 90%) in body weight for all animals.